Kursus Calon Pengantin (SUSCATIN) Dalam Membina Keharmonisan Rumah Tangga Di Kecamatan Metro Timur - Lili Purnamasari; Iwannudin Iwannudin (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, Indonesia, 2018)
Marriage is a sunnatullah that applies to all creatures of God, both humans, animals, and plants. Islam views that quality marriage will be measured from the process of pre, right, and post marriage. How someone starts the process of looking for a prospective wife or husband until the marriage contract and post-marriage will have offspring, all of which are clad in a clear Shari'a. So that the hope when having children, is that children who are pious and pious, can provide benefits to the people. Based on this matter, the Ministry of Religion took the initiative to implement the Candidate Candidate Course program in accordance with the government regulations that had been made.This research is a type of field research. The nature of this research is qualitative descriptive. In this study data collection methods used were observation, interview and documentation. In analyzing data, researchers used an inductive approach.The results of the study explained that what is meant by pre-marriage debriefing is the process of transforming behavior and attitudes in groups or the smallest social unit in society towards prospective brides. Quality marriage is a condition where marriage can produce happiness, conformity and stability of marriage. While the level of quality of marriage itself is influenced by factors such as optimal family composition, family life cycle, socio-economic feasibility and suitability of roles, social and personal resource factors of husband and wife even by premarital conditions. That the sakinah family is a family that all family members feel love, security, peace, protection, happiness, blessing, respect, respect, trust and blessed by Allah SWT.